The effects of hair regrowth with intravenous immunoglobulin (IVIG) therapy. Two case reports - Joseph A. Cahill; Mark I. Hewatt (Wolters Kluwer Medknow Publications, 2017)
Intravenous immunoglobulin (IVIG) is an immune modulating treatment used in a variety of immune mediated diseases. We report, two patients of different demographics, treated with IVIG for different neurological diagnoses who reported significant hair growth after starting IVIG treatments. To date, there have been no reports of using IVIG as a treatment for hair loss due to androgenic alopecia (AGA).